Peningkatan Hasil Belajar Siswa Melalui Model Problem Based Learning Pada Mata Pelajaran PAI di Kelas VIII SMPN 3 Kapur IX - Aulia Aulia; Salmiwati Salmiwati; Rina Mala Putri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
One of the goals of education is to increase the quantity and quality of students. In the learning process, the selection of the right learning model greatly affects the high and low learning outcomes of students. The learning model is a conceptual framework that describes learning procedures systematically to manage student learning experiences so that certain desired learning objectives can be achieved. The problem in this study is the low learning outcomes of students in Islamic Religious Education subjects, because the learning model used is still not varied. To overcome these problems, researchers applied the Problem Based Learning (PBL) model with the aim of improving Islamic Education learning outcomes in class VIII students of SMPN 3 Kapur IX. This research is class action research. The subjects in this study were students of class VII SMPN 3 Kapur IX which amounted to 22 students consisting of 20 male students and 7 female students. This research was carried out in three cycles, each cycle consisting of one meeting. Each cycle has four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it shows that the average learning outcomes of students have increased. It is known that the KKTP that has been determined by the school is 75. In pre-research, it is known that only 8 students are complete with a percentage of 29.63% and 19 students are not complete with a percentage of 70.37%. In cycle I it increased as many as 19 students who were complete with a percentage of 70.37% and 8 students who were not complete with a percentage of 29.63% Furthermore, in cycle II it also increased as many as 22 students reached a complete score with a percentage of 100%. Thus the Problem Based Learning (PBL) model can improve student learning outcomes in PAI subjects at SMPN 3 KAPUR IX.